How clonal differences and within-tree heterogeneity affect pore properties of hybrid aspen wood and biochar? - Turunen, Mika; Urbano-Tenorio, Fernando; Rasa, Kimmo; Hyväluoma, Jari; Rytkönen, Peetu; Kaseva, Janne; Beuker, Egbert; Suhonen, Heikki; Jyske, Tuula (Springer, 2021)
Production of applicable and homogeneous biochar for soil amendment purposes would benefit from knowledge on how feedstock heterogeneity impacts key biochar pore properties and how the properties are transformed due to pyrolysis. This study aimed (1) to quantify how clonal differences and within-tree heterogeneity of a hybrid aspen feedstock (wood) impact biochar pore properties and (2) to estimate how pore properties of non-pyrolysed wood materials are transformed when pyrolysed into biochar. The study was conducted by collecting samples from a hybrid aspen (Populus tremula L. × Populus tremuloides Michx.) clonal field trial. Key pore properties of non-pyrolysed and pyrolysed wood samples were quantified with 3D X-ray imaging and quantitative image analyses. The results demonstrated how pyrolysis shifted distinctively bi-modal pore size distributions of the wood samples towards smaller pore size regions. The bi-modal wood tissue structure controlled the pore structure also in the biochars. Due to decreasing cell wall thicknesses, the pyrolysis increased the porosity of the materials. While the thermal process homogenized differences in the wall thicknesses, the thicknesses of the feedstock were also shown to control the resulting thicknesses in the biochars. Mechanisms of biochar pore property formation can be considered important when designing applicable biochars for a chosen purpose. Clonal differences and within-tree heterogeneity had a direct impact only on the wall thicknesses and the pore diameters of vessels. These impacts can be of interest when planning feedstock utilization in biochar production. However, the results suggest that relatively homogeneous biochar can be produced from hybrid aspen feedstocks.
Keywords: 3D X-ray imaging; Microtomography; Poplar; Porosity; Wall thickness; Pyrolysis